The conditional contribution mechanism for repeated public goods: The general case - Joerg Oechssler; Andreas Reischmann; Andis Sofianos (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2019)
We present a new and simple mechanism for repeated public good environments. In the Conditional Contribution Mechanism (CCM), agents send two message of the form, "I am willing to contribute x units to the public good if in total y units are contributed." This mechanism offers agents risk-free strategies, which we call unexploitable. We prove that if agents choose unexploitable messages in a Better Response Dynamics model, all stable outcomes of the CCM are Pareto efficient. We conduct a laboratory experiment to investigate whether observed behavior is consistent with this prediction. In the complete information case we find that indeed almost 80% of outcomes are Pareto optimal. Furthermore, comparison treatments with the Voluntary Contribution Mechanism show that the CCM leads to significantly higher contribution rates. Even under incomplete information, contributions are fairly high and do not deteriorate over time.
Keywords: C72; C92; D82; H41; 330; Experimental Economics; Public Goods; Mechanism Design; Better Response Dynamics